The Effect of Mesenchymal Stem Cell-Derived Exosomes and miR17-5p Inhibitor on Multicellular Liver Fibrosis Microtissues - Farnaz Sani; Mina Soufi Zomorrod; Negar Azarpira; Masoud Soleimani (Hindawi Limited, 2023)
Background. Although several studies have been conducted on modeling human liver disease, it is still challenging to mimic nonalcoholic fatty liver disease in vitro. Here, we aimed to develop a fibrotic liver microtissue composed of hepatocytes, hepatic stellate, and endothelial cells. In addition, the therapeutic effects of umbilical cord mesenchymal stem cell-derived exosomes (UC-MSC-EXO) and anti-miR17-5p as new antifibrotic drugs were investigated. Methods. To create an effective preclinical fibrosis model, multicellular liver microtissues (MLMs) consisting of HepG2, LX2, and HUVECs were cultured and supplemented with a mixture of palmitic acid and oleic acid for 96 hr. Then, MLMs were exposed to UC-MSC-EXO and anti-miR17-5p in different groups. The results of cell viability, reactive oxygen species (ROS) production, liver enzyme levels, inflammation, and histopathology were analyzed to assess the treatment efficacy. Furthermore, the expression of collagen I (COL I) and α-smooth muscle actin (α-SMA) as critical matrix components, transforming growth factor beta (TGF-β), and miR-17-5p were measured. Results. Free fatty acid supplementation causes fibrosis in MLMs. Our results demonstrated that UC-MSC-EXO and anti-miR17-5p attenuated TGF-β1, interleukin-1β, and interleukin-6 in all experimental groups. According to the suppression of the TGF-β1 pathway, LX2 activation was inhibited, reducing extracellular matrix proteins, including COL I and α-SMA. Also, miR-17-5p expression was elevated in fibrosis conditions. Furthermore, we showed that our treatments decreased alanine aminotransferase and aspartate aminotransferase, and increased albumin levels in the culture supernatant. We also found that both MSC-EXO and MSC-EXO + anti-miR17-5p treatments could reduce ROS production. Conclusion. Our findings indicated that anti-miR17-5p and MSC-EXO might be promising therapeutic options for treating liver fibrosis. Furthermore, EXO + anti-miR had the best effects on boosting the fibrotic markers. Therefore, we propose this novel MLM model to understand fibrosis mechanisms better and develop new drugs.